(untitled) (Journal of Current and Advance Medical Research, 2019)
Background: Parkinson’s disease occurs in different socio-demographic characteristic people. Objective: The Purpose of the present study was to see the socio-demographic characteristics of Parkinson’s disease patients attended at a tertiary care hospital in Dhaka city. Methodology: This cross-sectional study was carried out in the in-patient and out-patient Department of Medicine and Neurology of Sir Salimullah Medical College and Mitford Hospital, Dhaka from July 2012 to December 2013 for a period of one and half year. All patients with Parkinson’s disease who were admitted under department of Medicine and Neurology and also who visited out-patient department of Medicine and Neurology of Sir Salimullah Medical College and Mitford Hospital, Dhaka were taken as study population. Patients who were diagnosed as Parkinson’s disease according to Brain Bank clinical criteria for diagnosis of Parkinson’s disease were included in this study. The demographic and socio-economic characteristics were recorded in a semi-structured questionnaire. Result: A total number of 40 Parkinson’s patients were recruited for this study. The mean age was 69.15±10.08 years. The male female ratio was found 1.22:1. The majority patients were businessman which was 13(32.5%) cases. The majority of 15(37.5%) patients came from rural area. However, 12(30.0%) patients were in primary level. Furthermore, 21(52.5%) patients came from lower class. Conclusion: In conclusion elder male rural dwellers are mostly suffering from Parkinson’s disease Journal of Current and Advance Medical Research 2019;6(2):106-110